Pengembangan Usaha Kelompok Peternak Lebah Trigona Ampel Mesari Banjar Bebali Desa Berembeng - I Gusti Ngurah Satria Wijaya; Ketut Gus Oka Ciptahadi; Ni Putu Meina Ayuningsih; Laser Narindro (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: The Trigona Beekeepers Group "Ampel Mesari" is a Trigona beekeeping group that accommodates breeders in the Be-bali Banjar area, Berembeng Village. The problems faced by this group are that the group's production process is still very minimal, and the method of packaging catfish honey products (trigona) still uses used bottles from other products and does not yet use product label packaging. The solution offered from this service activity is to provide production training to increase colonies from competent experts, provide superior bee colonies assistance, and packaging training with labeling. This community service project will be carried out through socializing exercises, core training activities, and monitoring and evaluation. Implementation of production training activities to increase bee colonies and product packaging and labeling training went well. It can be concluded that there was an increase in understanding, especially about the production of Trigona beekeeping and for an increase in understanding of product packaging and labeling, indicated due to the training participants' enthusiasm and happiness, the pretest and posttest values increased, and participants had no trouble understanding the material during the training process.            Keywords: trigona bee; production training; packaging and labeling training  Abstrak: Kelompok Peternak Lebah Trigona “Ampel Mesari” merupakan kelompok peternak lebah trigona yang mewadahi peternak-peternak yang berada diwilayah Banjar Bebali, Desa Berembeng. Permasalahan yang dihadapi oleh kelompok ini adalah proses produksi kelompok masih sangat minim sekali, dan cara pengemasan produk madu   trigona (kele) masih mempergunakan botol bekas produk lain serta belum menggunakan kemasan label produk. Pemecahan masalah yang diberikan dari program pengabdian ini adalah menawarkan pelatihan produksi untuk memperbanyak koloni dari pakar berkompeten, pemberian bantuan koloni lebah unggul, dan pelatihan kemasan dengan labeling. Metode pelaksanaan kegiatan pengabdian ini adalah melalui kegiatan sosialisasi, kegiatan inti berupa pelatihan, dan monitoring serta evaluasi. Pelaksanaan kegiatan pelatihan produksi untuk memperbanyak koloni lebah dan pelatihan pengemasan produk dan labeling berjalan dengan baik. Dapat disimpulkan bahwa terjadi transfer pengetahuan khususnya tentang produksi budidaya lebah trigona, pengemasan dan labeling produk diindikasikan dengan hasil tes yang menunjukkan peningkatan, serta peserta menyambut baik dan berse-mangat untuk mengikuti pelatihan ini sehingga tidak menemui kendala un-tuk memahami isi materi pelatihan kedua pelatihan. Kata kunci: lebah trigona; pelatihan produksi; pelatihan kemasan dan labeling